Potential mechanisms of formononetin against inflammation and oxidative stress: a review - Ding, Meiling; Bao, Yiwen; Liang, Huan; Zhang, Xiongwei; Li, Bin; Yang, Ruocong; Zeng, Nan (Frontiers in Pharmacology, 2024)
Formononetin (FMNT) is a secondary metabolite of flavonoids abundant in legumes and graminaceous plants such as Astragalus mongholicus Bunge [Fabaceae; Astragali radix] and Avena sativa L. [Poaceae]. Astragalus is traditionally used in Asia countries such as China, Korea and Mongolia to treat inflammatory diseases, immune disorders and cancers. In recent years, inflammation and oxidative stress have been found to be associated with many diseases. A large number of pharmacological studies have shown that FMNT, an important bioactive metabolite of Astragalus, has a profoundly anti-inflammatory and antioxidant potential. This review focuses on providing comprehensive and up-to-date findings on the efficacy of the molecular targets and mechanisms involve of FMNT and its derivatives against inflammation and oxidative stress in both in vitro and in vivo. Relevant literature on FMNT against inflammation and oxidative stress between 2013 and 2023 were analyzed. FMNT has antioxidant and anti-inflammatory potential and shows mild or no toxicity in various diseases. Moreover, in the medical field, FMNT has shown potential in the prevention and treatment of cancers, neurological diseases, fibrotic diseases, allergic diseases, metabolic diseases, cardiovascular diseases, gastrointestinal diseases and autoimmune diseases. Thus, it is expected to be utilized in more products in the medical, food and cosmetic industries in the future.